Honey bees: the queens of mass media, despite minority rule among insect pollinators. Issue 5 (14th June 2016) - Smith, Tobias J.; Saunders, Manu E.
Abstract: Pollination is a critical ecosystem function with high ecological and economic value. Conservation initiatives aimed at protecting diverse pollinator communities in natural and agricultural habitats are essential, but the implementation and success of such initiatives often depends on public support. Mass media play an important role in building public awareness around environmental issues, and biased coverage can have damaging effects. Here, we present the first analysis of how Australian mainstream media present the 'pollinator' paradigm. We gathered insect pollinator and pollination related articles from major Australian online newspapers published over a period of 9 years, and performed a qualitative content analysis using deductive coding to record information on the pollinator species or groups discussed in the story. We found 151 stories, and demonstrate that within these, there was a disproportionate focus on introduced European honey bees as the most important, or only, pollinator insect relevant to Australia. Only 15% of stories mentioned native bees as pollinators and 17% mentioned non‐bee pollinators. There is potential that the trend we report here for pollinators may be indicative of a larger overall simplification and neglect of biodiversity concepts in mainstream media, both in Australia and globally. As public awareness of science and environmental issues partly depend on disseminating accurate information beyond the scholar network, it is imperative that the broader effects of inaccurate science communication are fully understood.